Graphene Oxide as a Biocompatible and Osteoinductive Agent to Promote Implant Osseointegration in a Rabbit Tibia Model (Adv. Mater. Interfaces 28/2022). Issue 28 (4th October 2022) - Kwak, Jeong Min; Kim, Jungho; Lee, Chung‐Sung; Park, Il‐Soo; Lee, Min; Min, Dal‐Hee; Yeo, In‐Sung Luke
Abstract : Graphene Oxide as an Agent to Promote Implant Osseointegration Physicochemical modifications of grade‐IV commercially pure titanium surface by sandblasting, acid‐etching treatment and graphene oxide (GO) coating stimulate osteogenic activities of mesenchymal stem cells and improve biocompatibility to connective tissue cells. GO enhances bone healing and osseointegration at bone‐implant interface. This is reported by Dal‐Hee Min, In‐Sung Luke Yeom and co‐workers in article number 2201116 .